FACTORS AFFECTING SAVINGS AND INVESTMENT DECISIONS AMONG MAIZE FARMERS IN EKITI-STATE - OKE, J. T. O.; ADEYEMO , R.; ADESIYAN , O. F.; FADARE, O. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
This study analysed the factors affecting savings and investment decisions in Ekiti. Multi stage sampling technique was used to select 150 respondents for the study. Data was analysed using regression technique. The results showed that education, farming experience, farm size and net farm income had positively and significant effect on farmers savings while investment was significantly affected by age, education level, farming experience, farm size, interest rate and net income. Thus, increasing maize production beyond the subsistent level will raise farm income and enhance savings and investment participation of the farmers in the study area.